Role of e-Health in Imparting Continuing Medical Education to General Practitioners of Rural Areas of Sindh - Memon, Inayat Ullah; Usmani, Ambreen (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the effectiveness of e-Health in imparting continuing medical education to general practitioners of rural areas of Sindh. Study Design: Prospective comparative study Place and Duration of study: Department of Path, Indus Medical College, Tando Muhammad Khan, Pakistan from Feb to Jul 2021. Methodology: General Practitioners of any age group gender and working experience, presently practising in rural areas of Sindh, attended all five e-Health Continuing Medical Education sessions organized by the Department of Pathology. Before each online session, pre-tests and post-tests were conducted on completing each of the five online sessions. Scores of all preand post-session tests were calculated for analysis for each participant. Results: One hundred participants were included in the study, of which the majority (73%) were male compared to their counterparts. There was a statistically significant difference (p<0.05) between the pre and post-test scores of all study participants (24.92±6.98 and 30.91±6.19), respectively. While a statistically significant difference (p<0.05) between pre and posttest scores of male and female participants (24.47±6.43 and 26.11±8.31) and (30.64±5.62 and 31.62±7.59) respectively. Conclusion: Continuing e-Health medical education sessions revealed a significant improvement in general practitioners’ medical knowledge and professional competency, as reflected in the testing score.